A word in season : Isaiah's reception in the Book of Mormon - Spencer, Joseph M. (University of Illinois Press, 2023)
"The Book of Mormon's narrative privileges Isaiah over other sources, provocatively interpreting and at times inventively reworking the biblical text. Joseph M. Spencer sees within the Book of Mormon a programmatic investigation regarding the meaning and relevance of the Book of Isaiah in a world increasingly removed from the context of the times that produced it. Working from the crossroads of reception studies and Mormon studies, Spencer investigates and clarifies the Book of Mormon's questions about the vitality of Isaiah's prophetic project. Spencer's analysis focuses on the Book of Mormon's three interactions with the prophet: the character of Abinadi; the resurrected Jesus Christ; and the nation-founding figure of Nephi. Working from the Book of Mormon as it was dictated, Spencer details its vital and overlooked place in Isaiah's reception while recognizing the interpretation of Isaiah as an organizing force behind the Book of Mormon"--